APAVIT y turismo seguro post pandemia del Covid-19 - Meza Juárez, Víctor Andrés (2020)
The health crisis caused by the spread of COVID 19 has had an incalculable negative impact on the life and economy of millions of Peruvians and citizens around the world. A situation that also affected many industries, such as tourism: a sector that is experiencing the worst of its recessions in its history as a result of the compulsory social isolation caused by the pandemic. It is in this context that we believe that the new protocols established by governments and the proactivity of private companies, by adopting a new path to offer safe tourism for all, will be very valuable to rescue this industry from the depression it suffers from. But the corrective and preventive measures that the institutions are going to implement will not be the only recipe for success. It is necessary to re-open commercial activities progressively, segmenting a target audience and implementing successful communication that restores consumer confidence, which will awaken people's interest in leaving home and losing fear of the world in the one we live in. For this reason, we chose in this first post-crisis stage the millennials, a generation with a low risk of contagion and with a lifestyle that will add value to the restart of tourism